Teknologi Produksi Biogas dari Limbah Ternak untuk Memenuhi Kebutuhan Energi Rumah Tangga - Yusmiati Yusmiati; Bambang Singgih (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Livestock waste can reduce the quality of the environment if not managed properly, on the other hand livestock waste can be processed into a source of energy that can be utilized by the household. Livestock waste is processed into biogas by anaerobic fermentation process. Biogas is one of renewable energy and environmentally friendly. Biogas energy can be obtained from household waste water; liquid waste from chicken, cow, pig farms; organic waste from the market; food industry and so on. To convert livestock wastes into biogas, a series of devices called biogas reactors are needed. The use of a biogas reactor system has the advantage of reducing greenhouse gases, reducing odor, preventing the spread of disease, heat, power (mechanical / electrical) and byproducts of solid and liquid fertilizers. Biogas reactors are divided into three types: floating type, fixed dome type, and balloon type. The recommended type of biogas reactor for biogas processing of livestock waste is fixed dome type reactors because it has advantages such as construction cost is cheaper than floating reactor, can be done by breeder, more durable than balloon type reactor, and easier maintenance.